An overview of the cognitive implications of the Oldowan Industrial Complex. Issue 1 (2nd January 2018) - Toth, Nicholas; Schick, Kathy
ABSTRACT: This paper focuses on the empirical evidence for the cognitive abilities of early hominins of the Oldowan Industrial Complex ( c. ≥2.6 to 1.4 Mya) on the African continent. It profiles various researchers' approaches to and inferences about the cognitive abilities of Oldowan (Mode 1) toolmakers, based on the excavated archaeological evidence, primate models, experimental archaeology and neuroimaging techniques. Although there is a great deal of variation with regard to how to interpret such evidence, a variety of archaeological and palaeoneurological evidence indicates that Oldowan hominins represent a stage of technological and cognitive complexity not seen in modern great apes (chimpanzees, bonobos, gorillas, orangutans), but transitional between a modern ape-like cognition and that of later Homo ( erectus, heidelbergensis, sapiens ). Prevailing evidence and evolutionary models suggest that this new evolutionary stage entailed the growing elaboration of a problem-solving, technological niche that incorporated manufactured tools as a critical component of adaptation, especially to enhance food procurement and processing, as well as enhancements and greater complexity in social behaviours and communication.